Sinergitas Pemerintahan Pusat dan Pemerintahan Daerah Dalam Perumusan Kebijakan - Pardosi, Rodes Ober Adi Guna (Jurnal Legislasi Indonesia, 2023)
Policies in the scope of local authorities are a problem withinside the implementation of local autonomy. Emphasis at the synergy among the valuable and local governments is wanted with a view to expand rules which are still in concord with the rules completed through the central authorities. The idea of coverage is described as a based and systematic system. Policies in local government result in public offerings that offer great advantages for the prosperity of the people. In policy formula, the central and local governments have their respective roles. The feature of the central government as a facilitator, coordinating characteristic and carrying out the function of empowerment in relation to coverage system in the regions. The position of local governments as implementing activities in formulating a coverage have to be primarily based totally at the regulations of powerful and efficient policy formula. Communication among local governments and the central authorities is a shape of synergy this is needed nowadays so as to overcome various local coverage troubles that occur. Synergy goals in order that the rules taken do now no longer overlap every other, over-authorize and nevertheless take note of the general public interests in societ.Keywords: Policy Formulation, Central and Regional Relations, Policy Synergy AbstrakKebijakan dalam lingkup pemerintahan daerah menjadi perhatian dalam pelaksanaan otonomi daerah. Penekanan terkait sinergitas pemerintah pusat dan daerah diperlukan dalam rangka membangun kebijakan yang tetap memiliki harmonisasi dengan kebijakan yang dilakukan oleh pemerintah pusat. Konsep kebijakan dimaknai sebagai suatu sistem yang terstruktur dan sistematis. Kebijakan dalam pemerintahan daerah bermuara pada pelayanan publik yang memberikan manfaat yang besar demi kemakmuran rakyat. Dalam perumusan kebijakan, pemerintah pusat dan daerah memiliki peran masing-masing. Fungsi pemerintah pusat sebagai fasilitator, fungsi kordinasi dan menjalaakan fungsi pemberdayaan dalam kaitannya dengan perumusan kebijakan di daerah. Peran pemerintah daerah sebagai pelaksana kegiatan dalam merumusakan suatu kebijakan seyogianya berdasarkan kaidah perumusan kebijakan yang efektif dan efisien. Komunikasi antar pemerintah daerah dan pemerintah pusat merupakan bentuk sinergitas yang diperlukan dewasa ini demi mengatasi berbagai permasalahan kebijakan daerah yang terjadi. Sinergitas bertujuan agar kebijakan-kebijakan yang diambil tidak saling tumpah tindih, over kewenangan serta tetap memperhatikan kepentingan-kepentingan umum dalam masyarakat.